2018
DOI: 10.1093/ajcn/nqy117
|View full text |Cite|
|
Sign up to set email alerts
|

Serial measures of circulating biomarkers of dairy fat and total and cause-specific mortality in older adults: the Cardiovascular Health Study

Abstract: Long-term exposure to circulating phospholipid pentadecanoic, heptadecanoic, or trans-palmitoleic acids was not significantly associated with total mortality or incident CVD among older adults. High circulating heptadecanoic acid was inversely associated with CVD and stroke mortality and potentially associated with higher risk of non-CVD death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 63 publications
0
39
1
3
Order By: Relevance
“…Polyunsaturated FAs, such as C20:3 (n-6), C20:4 (n-6), C20:5 (n-3), C22:5 (n-3), C22:6 (n-6), were essentially absent from both cow and goat milk samples. As discussed in the introduction, it is becoming clear that each particular FA may play a different role in human health [6,[16][17][18]. In the case of saturated FAs, odd-chain saturated C15:0 and C17:0 have shown to be associated with a lower risk of type 2 diabetes [18].…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Polyunsaturated FAs, such as C20:3 (n-6), C20:4 (n-6), C20:5 (n-3), C22:5 (n-3), C22:6 (n-6), were essentially absent from both cow and goat milk samples. As discussed in the introduction, it is becoming clear that each particular FA may play a different role in human health [6,[16][17][18]. In the case of saturated FAs, odd-chain saturated C15:0 and C17:0 have shown to be associated with a lower risk of type 2 diabetes [18].…”
Section: (A)mentioning
confidence: 99%
“…However, recently Astrup and colleagues argued that these guidelines fail to take into account considerable evidence that the health effects vary for different types of saturated FAs and that the composition of the food source is crucially important [16]. It has been demonstrated that the high circulating odd-chain saturated fatty acid C17:0 is inversely associated with CVD and stroke mortality and potentially associated with higher risk of non-CVD death [17]. A recent large meta-analysis, which pooled the findings from 16 prospective cohort studies, has shown that higher levels of odd-chain saturated fatty acids C15:0 and C17:0 are associated with a lower risk of type 2 diabetes (T2D) [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, people tend to overestimate the intake of foods perceived as healthy and underreport the intake of foods perceived as less healthy (45) . Several fatty acids (C14 : 0, C15 : 0, C17 : 0 and trans-C16 : 1n-7) have been used as biomarkers of dairy intake (46)(47)(48) to overcome the shortcomings of FFQ. Combining the classic dietary assessment with validated dairy biomarkers may improve the robustness of dietary assessment in epidemiological studies.…”
Section: The Present Studymentioning
confidence: 99%
“…The result of a prospective cohort study in the United States on 2907 people over the age of 65 has been shown that there were no signi cant relationship between pentadecanoic, heptadecanoic and trans-palmitoleic phospholipids (as biomarkers of dairy fat intake) with total mortality and incidence of CVDs [30]. In another meta-analysis study of 13 studies, it was observable that higher intake of dairy fat was not associated with an increased risk of cardiovascular disease [31] .…”
Section: Buttermentioning
confidence: 99%